A novel umami electrochemical biosensor based on AuNPs@ZIF-8/Ti3C2 MXene immobilized T1R1-VFT. (15th December 2022) - Liu, Jing; Zhang, Ninglong; Li, Jiansen; Li, Mingyang; Wang, Guangxian; Wang, Wenli; Fan, Yuxia; Jiang, Shui; Chen, Gaole; Zhang, Yin; Sun, Xia; Liu, Yuan
Highlights: A novel umami biosensor based on AuNPs@ZIF-8/Ti3 C2 MXene was first constructed. The synergy of AuNPs@ZIF-8 and Ti3 C2 MXene enhanced the sensor performance. A wide linear range of 10 −11 –10 −3 M was achieved at the umami biosensor. The biosensor was applied to analyze the synergistic effects of umami substances. Abstract: The bioelectronic tongues based on taste receptors have been emerging with human-like taste perception. However, the practical applications of the receptor-based biosensors were restricted by their narrow and low dynamic ranges. Here, a novel immobilization strategy based on AuNPs@ZIF-8/Ti3 C2 MXene was developed to immobilize the umami ligand binding domain (T1R1-VFT), to fabricate an umami biosensor for umami substances detection. Through the synergic effect of AuNPs@ZIF-8 and Ti3 C2 MXene, the capacity to load T1R1-VFT was effectively increased, and the response signal was also amplified by approximately 3 times. The proposed biosensor showed an ultrawide dynamic range of 10 −11 –10 −3 M, and a high upper limit of detection, which was closer to the human taste threshold and suitable for detecting foods rich in umami substances. Additionally, the biosensor was successfully applied to detect real samples and analyze the synergistic effects of binary umami substances.